IMPLEMENTASI PENGGUNAAN AKUN BELAJAR.ID DALAM PEMBELAJARAN JARAK JAUH PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI - Ariana Setyo Sejati; Laila Ngindana Zulfa; Nur Rois (Universitas Wahid Hasyim Semarang, 2022)
ABSTRACTThe launch of a learning.id account which is expected to help learning activities, but in reality there are still many schools that do not activate a learning.id account and do not use the facility as well as possible. SMPN 1 Mranggen is one of the schools in Demak Regency where most of the educators, teaching staff and students have activated a learning.id account.The formulation of this research is to find out how the preparation, process and results of the Implementation of the Use of Learning Accounts. Id in Distance Learning in Islamic Religion and Moral Education Subjects at SMPN 1 Mranggen. The purpose of this study was to describe the preparation, process and results of the implementation of the Implementation of the Use of Learning Accounts. Id in Distance Learning in Islamic Religion and Character Education Subjects at SMPN 1 Mranggen. This research is a phenomenological qualitative research. The data in this study were obtained from observations, interviews, and documentation.The results of this study indicate that the application of learning accounts. en for distance learning in the subject of Islamic Religious Education and good manners in the subjects of Islamic Religious Education and manners at SMPN Mranggen are (1) the implementation of the learning.id account has been carried out at SMP N 1 Mranggen according to the plan. The plan begins by forming a special team that handles learning.id accounts, (2) In implementing distance learning on Islamic Religious Education subjects, educators and students have taken advantage of the features contained in the learning.id account, (3) Constraints The problem faced in implementing the learning.id account implementation for educators is the lack of mastery of knowledge about the use of information technology, while for students the obstacles are caused by a weak internet signal, limited internet quota, and student mastery in utilizing features. contained in the program. learning.id account and lack of student knowledge in changing settings on cellphones to change personal accounts to learning.id accounts.The conclusion from the research on the implementation of the use of learning.id accounts in distance learning in the subjects of Islamic Religious Education and Morals at SMPN 1 Mranggen shows that they have carried out learning activities by utilizing the learning.id account by using the google classroom, google meet, google form and google features. DriveKata Kunci: Implementation, belajar.Id, Distance Learning, PAI